(untitled) (International Journal of Physiotherapy, 2016)
Background: Osteoarthritis (OA) is the most common type of joint disease. Pain is the most common symptom of knee osteoarthritis. Also it characterized by sign, symptoms of inflammation, pain, stiffness and loss of mobility. This study was conducted to explore the efficacy of kinesio taping (KT) versus Aescin, Diethylamine Salicylate gel phonophoresis (PH) on pain level, range of motion (ROM), and proprioceptive accuracy on mild to moderate knee OA patients. Methods: Forty females with knee OA from Outpatient Clinic of Physical Therapy Faculty participated in the study with mean age (49±5.82) years. They were randomly assigned into 2 equal groups. Group I: received Aescin, Diethylamine Salicylate gel PH with pulsed ultrasound therapy and group II received KT. All patients received hot packs and selected exercise program for four weeks; three sessions per week. Visual analogue scale was used in assessment of pain level. Electronic digital goniometer was used in assessment of knee flexion ROM. Iso-kinetic daynamometer was used in assessment of knee proprioceptive accuracy. Results: There was a significant relieving of pain perception, increasing of knee flexion ROM and improving proprioceptive accuracy in knee joint post-study in both groups. But application of Aescin, Diethylamine Salicylate gel PH had significant relieve of knee pain than KT. Conclusion: Using of Aescin, Diethylamine Salicylate gel PH is more effective than KT application in reliving knee pain in knee osteoarthritic patients.